A Novel lncRNA, AK130181, Contributes to HIV-1 Latency by Regulating Viral Promoter-Driven Gene Expression in Primary CD4+ T Cells - Haiyu Li; Xiangbo Chi; Rong Li; Jing Ouyang; Yaokai Chen (Elsevier, 2020)
The functions and mechanisms of long non-coding RNAs (lncRNAs) in latent HIV-1 infection are not yet fully understood and warrant further research. In this study, we identified the newly inhibitory lncRNA AK130181 (also named LOC105747689), which is highly expressed in CD4+ T lymphocytes latently infected with HIV, using bioinformatics. We also found that AK130181 is involved in HIV-1 latency by inhibiting long terminal repeat (LTR)-driven HIV-1 gene transcription in a nuclear factor κB (NF-κB)-dependent manner. Furthermore, silencing AK130181 significantly reactivates viral production from HIV-1 latently infected Jurkat T cells and primary CD4+ T cells. Interestingly, we found that inhibition of AK130181 in resting CD4+ T cells from HIV-1-infected individuals treated with highly active antiretroviral therapy significantly increased viral reactivation upon T cell activation in vivo. We provide new insights and a better understanding of lncRNAs that play a role in HIV-1 latency, and suggest that silencing AK130181 expression to activate HIV-1 latently infected cells may be a potential therapeutic target for HIV-infected individuals.